Distinguishing kerogen and oil cracked shale gas using H, C-isotopic fractionation of alkane gases. (March 2018) - Liu, Quanyou; Jin, Zhijun; Wang, Xiaofeng; Yi, Jizheng; Meng, Qingqiang; Wu, Xiaoqi; Gao, Bo; Nie, Haikuan; Zhu, Dongya
Abstract: The formation mechanism of 23 shale gas samples from the Fuling shale gas field in the Upper Ordovician Wufeng (O3 w) Formation-Lower Silurian Longmaxi (S1 l) Formation marine shales was investigated based on the carbon and hydrogen isotopes of methane, ethane, and propane. Fuling shale gas is mainly composed of alkane gases, and has a dryness coefficient, C1 /C1-3, of 0.992–0.993. The reversed carbon isotopic trend where δ 13 C1  >  δ 13 C2 is a typical characteristic indicating mixing of kerogen cracked gas and crude oil cracked gas. The empirical correlations between ln (C1 /C2 ) vs. ln (C2 /C3 ) and ln (C1 /C2 ) vs. δ 13 C of alkane gases at different thermal maturity levels were used to distinguish kerogen cracked gas from crude oil cracked gas. Five stages of kerogen cracking and crude oil cracking were identified with a wide range of thermal maturities (vitrinite reflectance %Ro ): 1) %Ro  < 0.8: shale gas showed a normal isotopic trend ( δ 13 C1  <  δ 13 C2 ) and was dominated by primary kerogen cracking; 2) %Ro of 0.8–1.5: primary kerogen cracking ended, and crude oil cracking was initiated, which is associated with a normal isotopic trend of methane and ethane ( δ 13 C1  <  δ 13 C2 ); 3) %Ro of 1.5–1.8: the gas is the mixture of gases from both late kerogen cracking and oil cracking, with an initially reversed carbon isotopic trend of δ 13 C1  >  δ 13 C2 ; 4) %Ro of 1.8–2.5: residual kerogen cracking proceeded to generate CH4, and light oil cracking generated heavier gaseous hydrocarbons, with a completely reversed carbon isotopic trend of alkane gases ( δ 13 C1  >  δ 13 C2  >  δ 13 C3 ); 5) %Ro  > 2.5: further cracking of heavier gaseous hydrocarbons generated CH4 . Highlights: Shale gas origins were analysed using C and H isotopes of methane and ethane. Fuling shale gas is dominantly oil cracked gas with some mixed kerogen cracked gas. We classified five thermal maturity stages of kerogen, oil, and mixed cracked gas. Mixed kerogen and oil cracked gas leads to reversal of CH4 and C2 H6 carbon isotopes.